Special Psychology and Pedagogy in the Modern School. - Lubovsky D. V. (Moscow State University of Psychology and Education, 2015)
The article points out that need in improving competence in the field of special pedagogy and psychology for employees of school education dramatically increased and calls the causes of this phenomenon. Methodological and methodical principles of training of teachers and the forming their competence in the field of special psychology and pedagogy are outlined. Concepts of cultural-historical theory ("growing in the culture" of the child, the zone of proximal development, primary and secondary disorders, mediation), the activity approach leading activity and amplification of its development), theory of developmental education are suggested to be methodological bases. The article substantiates the need for formation of competence in the field of general and specific patterns of abnormal development and relying on the knowledge of the educational requirements specific to people with special needs. The article points out the possibilities of using the innovative teaching methods in the trainings for teachers in order to build competencies in the field of special pedagogy and psychology